Improved outcome of acute severe ulcerative colitis while using early predictors of corticosteroid failure and rescue therapies. Issue 6 (June 2016) - Llaó, Jordina; Naves, Juan E.; Ruiz-Cerulla, Alexandra; Gordillo, Jordi; Mañosa, Míriam; Maisterra, Sandra; Cabré, Eduard; Garcia-Planella, Esther; Guardiola, Jordi; Domènech, Eugeni
Abstract: Background and aim: Intravenous corticosteroids remain the first line therapy for severe attacks of ulcerative colitis although up to 30–40% of patients do not respond to treatment. The availability of alternative therapies to colectomy and the knowledge of early predictors of response to corticosteroids should have improved the clinical outcomes of patients with severe refractory ulcerative colitis. The aim of the study is to describe the current need, way of use, and efficacy of rescue therapies, as well as colectomy rates in patients with severe ulcerative colitis flares. Methods: Between January 2005 and December 2011, all patients admitted in three referral centres for a severe ulcerative colitis flare who received intravenous corticosteroids were identified and clinical and biological data were accurately collected. Patients were followed-up until colectomy, death, or date of data collection. Results: Sixty-two flares were included. Initial efficacy of intravenous corticosteroids (mild activity or inactive disease without rescue treatment, at day 7 after starting intravenous corticosteroids) was achieved in 50% of flares, and rescue therapies were used in 27 episodes (43%). After a median follow-up of 18 months, the colectomy rate was 6.5%. Failed oral corticosteroids for the index flare were the only baseline feature that predicted the need for rescue therapy and colectomy. Conclusions: There is a marked reduction in the colectomy rate and an increased use of medical rescue therapies as compared to historical series. Patients worsening while on oral corticosteroids for a moderate flare are at high risk of rescue therapy and colectomy and, therefore, should be directly treated with rescue therapies instead of attempting intravenous corticosteroids.